2019
DOI: 10.3390/agronomy9120791
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Efficiency of Vermicompost Derived from Different Biowastes on Wheat (Triticum aestivum L.) Plant Growth and Soil Health

Abstract: The present study was conducted to explore the role of different types of vermicomposts (VCs) prepared from different substrates to improve soil health (physical and chemical properties) and wheat plant growth under field conditions. Different combinations of vermicompost prepared from different substrates (cow dung, paper waste, and rice straw) and inorganic fertilizers were applied in soil using wheat as a test plant. The impact of three different VCs on physico-chemical characteristics and nutrient availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Wang et al [27] showed that applying slow-release fertilizer resulted in reduced NPK rates being needed for optimum production, while increasing yield and net return for fertilization of chives. Aslam et al [28] demonstrated increased wheat yield and yield components with application of NPK + vermicompost compared to NPK alone.…”
Section: Nutrient Sourcesmentioning
confidence: 99%
“…Wang et al [27] showed that applying slow-release fertilizer resulted in reduced NPK rates being needed for optimum production, while increasing yield and net return for fertilization of chives. Aslam et al [28] demonstrated increased wheat yield and yield components with application of NPK + vermicompost compared to NPK alone.…”
Section: Nutrient Sourcesmentioning
confidence: 99%
“…Traditionally, vermicomposts are produced from cattle manure with the addition of organic carbon-rich biomass, such as grass or straw [6], but it is possible to use different organic waste materials and byproducts for its production. The possibility for successful application of different types of vermicompost for the production of various crop species has been shown for vermicomposts produced from agricultural waste [7], byproducts of food production or food waste [8,9], urban organic waste [10], and composted sewage sludge [11].…”
Section: Introductionmentioning
confidence: 99%
“…A randomized complete block design with three replications was used in the experiment and manures were applied in the same field during both years. The size of the gross plot was 8 m × 10 m. There were eight organic manure application treatments: (1) control (no manure), (2) press mud 10 t ha −1 (Hammad et al 2011), (3) vermicompost 10 t ha −1 (Roberts et al 2007;Joshi et al 2013;Aslam et al 2019), (4) farmyard manure 10 t ha −1 (Mishra et al 2006;Hammad et al 2011), (5) press mud 5 t ha −1 + vermicompost 5 t ha −1 , (6) press mud 5 t ha −1 + farmyard manure 5 t ha −1 , (7) vermicompost 5 t ha −1 + farmyard manure 5 t ha −1 , and (8) press mud 3.3 t ha −1 + vermicompost 3.3 t ha −1 + farmyard manure 3.3 t ha −1 . Press mud was obtained from Husein Sugar Mills, Jaranwala, Punjab, Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…Vermicompost is a good choice as a substitute for chemical fertilizers in sustainable agriculture. It has been reported that vermicompost application was found to improve crop growth and yield of rice (Bejbaruah et al 2013), maize (Guo et al 2015), potato (Alam et al 2007), sorghum (Hameeda et al 2007), and wheat (Roberts et al 2007;Kizilkaya et al 2012;Joshi et al 2013;Ibrahim et al 2015;AlAmin et al 2017;Aslam et al 2019;Erdal and Erdal and Ekinci 2020).…”
Section: Introductionmentioning
confidence: 99%